Factors influencing adherence to iron and folic acid among primigravidae seeking antenatal care in Mbarara district, Southwestern Uganda. A cross-sectional study. - Ankunda, Hector; Ashaba , Shillah; Prosper , Victor; Amanyire, Jordan; Matovu, Daniel (Student's Journal of Health Research Africa, 2025)
Background This study aimed at determining the factors influencing adherence to iron and folic acid among primigravidae seeking antenatal care in Mbarara district, Southwestern Uganda. Methods This was a cross-sectional study done within Mbarara district among primigravidae seeking antenatal care. Proportionate probability sampling and simple random sampling techniques were used to select 172 primigravidae seeking antenatal care in Mbarara district. Interviews were done using a researcher-administered questionnaire with a quantitative approach. Data was entered in Excel, cleaned, and exported to Stata version 17 for analysis. Logistic regression was used to determine factors associated with adherence to iron and folic acid supplements among primigravidae. Results The proportion of primigravidae attending antenatal care in Mbarara district whose adherence to iron and folic acid supplements was defined as taking at least 80% of the prescribed iron and folic acid supplements was 64.53% (95% CI 0.52 – 0.63). Adherence was associated with age bracket 20-29 years (AOR=4.57, 95%CI: 2.05-11.13), having a reminder to take iron and folic acid supplements (AOR=2.81, 95% CI: 1.33-5.92) and being counselled on the importance of taking iron and folic acid supplements (AOR=4.45, 95% CI: 2.07-9.31). Conclusions The level of adherence to iron and folic acid supplements among primigravidae attending ANC in Mbarara district is relatively high (6 in every 10 primigravidae). Primigravidas who are less than 30 years old, with a reminder to take iron and folic acid supplements and counselling from health workers about the importance of iron and folic acid supplements during pregnancy, are more likely to adhere to iron and folic acid supplements. Recommendation Intensive and daily counselling about the importance of iron and folic acid supplements during pregnancy should be done by antenatal care providers, especially to primigravidae who are 30 years of age or older.